2017
DOI: 10.1002/jcb.26509
|View full text |Cite
|
Sign up to set email alerts
|

Long non‐coding RNA cox‐2 prevents immune evasion and metastasis of hepatocellular carcinoma by altering M1/M2 macrophage polarization

Abstract: Macrophages have been shown to demonstrate a high level of plasticity, with the ability to undergo dynamic transition between M1 and M2 polarized phenotypes. We investigate long non-coding RNA (lncRNA) cox-2 in macrophage polarization and the regulatory mechanism functions in hepatocellular carcinoma (HCC). Lipopolysaccharide (LPS) was used to induce RAW264.7 macrophages into M1 type, and IL-4 was to induce RAW264.7 macrophages into M2 type. We selected mouse hepatic cell line Hepal-6 and hepatoma cell line He… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
146
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 181 publications
(154 citation statements)
references
References 44 publications
(89 reference statements)
0
146
3
Order By: Relevance
“…Twenty‐four hour later, the supernatant was collected. CD86 (BioLegend, San Diego, CA) as a surface marker of the M1 phenotype macrophages, and CD206 (BioLegend) as a surface marker of the M2 phenotype macrophages were identified by flow cytometry in LPS‐treated macrophages or IL‐4‐treated macrophages . Anti‐IL‐6 antibody (Sigma Chemical Co., St. Louis, Missouri) neutralized by IL‐6 (0.5 μg/mL) was added to RAW264.7 macrophages to react for 48 hours, and then LPS and IL‐4 were supplemented to induce M1 or M2 phenotype macrophages.…”
Section: Methodsmentioning
confidence: 99%
“…Twenty‐four hour later, the supernatant was collected. CD86 (BioLegend, San Diego, CA) as a surface marker of the M1 phenotype macrophages, and CD206 (BioLegend) as a surface marker of the M2 phenotype macrophages were identified by flow cytometry in LPS‐treated macrophages or IL‐4‐treated macrophages . Anti‐IL‐6 antibody (Sigma Chemical Co., St. Louis, Missouri) neutralized by IL‐6 (0.5 μg/mL) was added to RAW264.7 macrophages to react for 48 hours, and then LPS and IL‐4 were supplemented to induce M1 or M2 phenotype macrophages.…”
Section: Methodsmentioning
confidence: 99%
“…This study indicated that TCONS_00019715 promotes macrophage polarization to the M1 phenotype. LncRNA COX‐2 is more highly expressed in M1 macrophages and increases the expression levels of IL‐12, iNOS, and TNF‐α . A recent study has shown that lncRNA GAS5 suppresses IFN regulatory factor 4 (IRF4) transcription by binding polycomb repressive complex 2 (PRC2) to inhibit M2 polarization …”
Section: Modulation Of M2b Macrophage Polarizationmentioning
confidence: 99%
“…Another study showed that as a coactivator of NF‐kB, lincRNA‐Cox2 functions as a regulator of the late phase of the primary immune response via modulation of epigenetic chromatin remodeling . Intriguingly, lincRNA‐Cox2 has been shown to modulate both the activation and the repression of distinct classes of immune genes in innate immune cells …”
Section: Introduction Of Lncrnasmentioning
confidence: 99%